An overview on the preparation of rice husk biochar, factors affecting its properties, and its agriculture application - Karam Singh, Daljit Singh; Nagabovanalli, Prakash; Rajoo, Keeren Sundara; Ishak, Che Fauziah; Abdu, Arifin; Rosli, Zamri; Muharam, Farrah Melissa; Zulperi, Dzarifah (Elsevier, 2021)
In rice-producing countries, the abundance of rice residue must be sustainably managed to avoid environmental problems. Moreover, repeated usage of inorganic fertilizers has caused rapid soil deterioration in these arable lands. Converting rice husk residue into rice husk biochar (RHB) and reapplying it back to paddy fields as a soil amendment can be a sustainable approach in rice production. Due to its adsorptive capability, nutrient retention capacity and high silica content, RHB can improve soil fertility and improving the effectiveness of fertilizer when mixed together due to its nutrient retention capacity and high silica content. High silica content in rice husk biochar provides better nutrient retention, turgidity, and structure for plant. The objectives of this review article are to compile studies related to rice husk biochar properties and factors affecting it and application of rice husk biochar in Asian agriculture.